The regional forecasting systems of the Italian seas. (12th February 2016) - Napolitano, E.; Iacono, R.; Sorgente, R.; Fazioli, L.; Olita, A.; Cucco, A.; Oddo, P.; Guarnieri, A.
ABSTRACT: Over the last 15 years, five operational systems for the forecasting of the circulation of the Italian seas have been developed, which provide products of use for the management and safety of marine activities and for the protection of the marine environment. The first systems which focused on the Adriatic Sea and the Sicily Strait, have been added to over the years, to cover the Tyrrhenian Sea, the seas around Sardinia, and, finally, the region around the Bonifacio Strait, a small area interested by an intense marine traffic. In this work, the main features of the five regional systems are described and examples are given of their capabilities and their use for revealing new features of marine circulation.